2021
DOI: 10.1016/j.tet.2021.132159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phosphonate derivatives of 2′-deoxy-2′-fluorotetradialdose d-nucleosides and tetradialdose d-nucleosides

Abstract: Analogs of nucleosides and nucleotides represent a promising pool of potential therapeutics. This work describes a new synthetic route leading to 2'-deoxy-2'-fluorotetradialdose D-nucleoside phosphonates. Moreover, a new universal synthetic route leading to tetradialdose d -nucleosides bearing purine nucleobases is also described. All new compounds were tested as triphosphate analogs for inhibitory potency against a variety of viral polymerases. The fluorinated nucleosides were transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The final deprotection of protecting groups led to compound 205 (Scheme 17). These compounds did not show any biological activities [41] …”
Section: Sugar Fragment Modified Analoguesmentioning
confidence: 89%
See 1 more Smart Citation
“…The final deprotection of protecting groups led to compound 205 (Scheme 17). These compounds did not show any biological activities [41] …”
Section: Sugar Fragment Modified Analoguesmentioning
confidence: 89%
“…These compounds did not show any biological activities. [41] Calenbergh and group synthesized a series of 3'-fluoro 7deaza nucleoside derivatives with 3'-deoxy-3'-ribofuranosyl and xylofuranosylnucleosides. Fluro substituents were introduced by using DAST on substrates 207 and 221 which provided inverted fluoro sugar derivatives 208 and 222.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…The use of thiophenyl-glycosyl donors such as II was also envisioned to perform the decisive O -glycosylation step under milder conditions and for the stability of thioglycosides toward a host of conditions, including strongly acidic ones . While examples of selective O -, C -, or N -glycosylation reactions of bifunctional glycosides have been reported in the literature, , the use of 1,5-bis-glycopyranosides of type I and II is surprisingly uncommon to the best of our knowledge. In the early 2000s, Wei et al reported the synthesis of a diversity of C-5-substituted l -sugars by the addition of various nucleophiles to 1- O -methyl-4-epoxypyranosides (Scheme a) …”
Section: Introductionmentioning
confidence: 99%
“…In the furanose series, Lewis acid-promoted reactions with various C - or N -nucleophiles were performed on acetate glycosyl donors in which the hydroxy group of the second reducing end is protected as an alkyl ether or by acetonation of the 1,2-OH groups of the glycosyl donors (Scheme b,c). , As shown above, glycosylation reactions of 1,5-bis-glycopyranosides or 1,4-bis-glycofuranosides were reported only with glycosyl donors in which the relative reactivity of the two anomeric leaving groups is noticeably different to permit the selective functionalization of one anomeric center in the presence of the other one. It was thus anticipated that the key Fries-type rearrangement could be problematic with 1,5-bis-glycopyranosides of type I even though phenyl glycopyranosides are known to be hydrolyzed more rapidly than methyl glycopyranosides .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation